ANALISIS PEMANFAATAN ICT DALAM PEMBELAJARAN FISIKA SMA DI KOTA PEKANBARU - Novria, Nurul; Z Zulirfan, Z Zulirfan; Fakhruddin Z, Fakhruddin Z (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to identify the types of ICT utilization and the constraints of the use of ICT in learning physics. This survey also describe the level of ICT utilization and the level of obstacles faced by physics teacher in using ICT in learning. This type of research is a survey research. The subjects of this study were 20 physics teachers from 20 SMA and MA in Pekanbaru. Data collection techniques in the form of distributing questionnaires online. This instruments contain 20 statement items. Data analysis of this study uses descriptive analysis, which provides an overview of the level of ICT utilization and the constraints of using ICT in learning physics. We found that the average percentage of the level of ICT utilization in physics learning in Pekanbaru was 55% in the medium category. While, the percentage for the level of obstacles in using ICT in learning physics was 61% with a high category.Key Words: Utilization of ICT, physics learning, the constraints of using ICT.